Analisis Manajemen Risiko pada UMKM DuaTiloe Barbershop - Ghulam Priyatna Yoniar; Reihan Ahmad Nurhakim; Aris Kurniawan; Elky Rimba Priatna; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study aims to analyze the implementation of risk management at the micro, small, and medium enterprise (MSME) DuaTiloe Barbershop as an effort to maintain business continuity and competitiveness within the barbershop service industry. The research employed a descriptive qualitative method by collecting data through interviews and observations with the owner and employees. The analysis was conducted using the ISO 31000 framework and SWOT analysis to identify internal and external factors influencing business risks. The results show that the main risks faced include market, operational, and human resource (HR) risks. DuaTiloe Barbershop manages these risks through service innovation, cost-efficiency strategies, regular training for barbers, and an incentive system to maintain employee loyalty. The implementation of preventive and adaptive measures has proven to enhance operational stability and strengthen the business image. Therefore, effective risk management serves as a key factor in supporting the sustainability and growth of MSMEs in the service sector.